Integrating augmented reality visualisation in the implementation of blended learning: showcases of two experimentations - Abdullah, Fadzidah; Kassim, Mohd Hisyammudin; Abdul Razak, Mohd Raziff; Sanusi, Aliyah Nur Zafirah (2017)
In the attempt to implement Blended Learning (BL) in architectural education, various efforts have been initiated, including in architectural visualization of building construction details. Augmented Reality (AR) has immense potential to produce spectacular architectural visualization and representation; hence, it could be integrated with the current trend of Blended Learning. This research assesses the integration of AR visualization with Blended Learning in architectural education, by experimenting techniques of AR application in the teaching and learning of building construction courses. Two (2) projects have been carried out to experiment the integration techniques, and assessment would be made to examine the strength of the integration as attributes for successful learning. This research uses qualitative research approach to have the explorative inquiry of the experimentation, focusing on tentative usages of AR in two (2) construction courses of steel and timber. Meanwhile, quantitative research approach has also been applied to this research by having survey questionnaires to obtain students’ feedback on their acceptance on the integration. Data from the two experimentations would be analyzed and compared to generate conclusive idea on the potential of integrating AR with Blended Learning to enhance the teaching and learning of architecture. This research found that AR has been successfully integrated with blended learning and most students who participated in the two experimentations favour AR, as features of blended learning, to be continuously implemented in the teaching and learning of architectural education.